Impact of Financial Distress, Firm Size, Fixed Asset Intensity, and Inventory Intensity on Tax Aggressiveness - Amalia Ahdiyah; Dedik Nur Triyanto (Universitas Padjadjaran, 2021)
This study analyses the impact of financial distress, firm size, fixed asset intensity, and inventory intensity on tax aggressiveness in consumer products companies listed in the Indonesia Stock Exchange (IDX) from 2015-2019. The total population of listed consumer products companies was forty-one. The technique of sampling used is purposive sampling. In total, twenty-seven companies were obtained with 135 data set for five years. This study used quantitative methods, and the data analysis technique in this study was panel data regression analysis. This study indicates that financial distress, firm size, fixed asset intensity, and inventory intensity simultaneously affect tax aggressiveness. Meanwhile, firm size and fixed asset intensity positively impact tax aggressiveness. However, financial distress and inventory intensity have no impact on tax aggressiveness. The government is encouraged to pay more attention to those affecting factors.